Autophagy-Related Gene 7 Polymorphisms and Cerebral Palsy in Chinese Infants - Xia, Lei; Xu, Jianhua; Song, Juan; Xu, Yiran; Zhang, Bohao; Gao, Chao; Zhu, Dengna; Zhou, Chongchen; Bi, Dan; Wang, Yangong; Zhang, Xiaoli; Shang, Qing; et al. (Frontiers in Cellular Neuroscience, 2019)
Cerebral palsy (CP) is a group of non-progressive motor impairment syndromes that are secondary to brain injury in the early stages of brain development. Numerous etiologies and risk factors of CP have been reported, and genetic contributions have recently been identified. Autophagy plays an important role in brain development and pathological conditions, and autophagy-related gene 7 (ATG7) is essential for autophagosome biogenesis. The purpose of this study was to explore the genetic association between ATG7 gene single nucleotide polymorphisms (SNPs) and CP in Han Chinese children. Six SNPs (rs346078, rs1470612, rs11706903, rs2606750, rs2594972 and rs4684787) were genotyped in 715 CP patients and 658 healthy controls using the MassArray platform. Among them, 73 CP patients and 79 healthy controls were selected for plasma ATG7 measurement. The differences in the allele and genotype frequencies of the rs1470612 and rs2594972 SNPs were determined between the CP patients and controls (pallele = 0.02 and 0.0004, pgenotype = 0.044 and 0.0012, respectively). Subgroup analysis revealed a more significant association of rs1470612 (pallele = 0.004, pgenotype = 0.0036) and rs2594972 (pallele = 0.0004, pgenotype < 0.0001) with male CP, and more significant differences in allele and genotype frequencies were also observed between CP patients with spastic diplegia and controls for rs1470612 (pallele = 0.0024, pgenotype = 0.008) and rs2594972 (pallele < 0.0001, pgenotype = 0.006). The plasma ATG7 level was higher in CP patients compared to the controls (10.58 ± 0.85 pg/mL vs. 8.18 ± 0.64 pg/mL, p = 0.024). The luciferase reporter gene assay showed that the T allele of rs2594972 SNP could significantly increase transcriptional activity of the ATG7 promoter compared to the C allele (p = 0.009). These findings suggest that there is an association between genetic variants of ATG7 and susceptibility to CP, which provides novel evidence for the role of ATG7 in CP and contributes to our understanding of the molecular mechanisms of this neurodevelopmental disorder.